Modern approaches to the treatment of constipation in pregnant women - A. K. Minaeva (Лечащий Врач)
Background. Constipation, or constipation, is a polyetiological pathological condition characterized by prolongation of the intervals between acts of defecation and changes in the shape and consistency of fecal matter. The incidence of this pathology is very high all over the world, mainly depending on the nature of nutrition, hypodynamia, standard of living and availability of medical care in different regions of the world. Special attention is paid to the problem of constipation in pregnant women, as it is not only a matter of quality of life, constipation can affect the course of pregnancy and even contribute to its termination. Constipation is one of the most frequent pathologies of the gastrointestinal tract and can occur in 11-62% of pregnant women. The article presents factors predisposing to the development of constipation in each trimester, explains its mechanisms, describes possible complications of chronic constipation in expectant mothers and the negative impact on the course of pregnancy and in the postpartum period.Results. Approaches to the diagnosis of constipation according to modern classifications, including the "Rome criteria for constipation" 2016, are shown. Special attention is paid to the prevention of constipation in pregnant women. The importance and expediency of a comprehensive approach to the prevention and treatment of constipation in expectant mothers, namely, changing the nature and diet, the level of physical activity in the absence of contraindications and adequate choice of drugs approved for use during pregnancy. A comparative analysis of the use of the most common drugs (lactulose and psyllium) by two groups of pregnant patients is given, the mechanisms of action and effectiveness of psyllium in the treatment of constipation, as well as some other positive properties of psyllium and its tolerance by pregnant women are noted. Clinical examples of effective therapy of constipation in expectant mothers with the use of a medicinal preparation containing plantain ovata (Plantago ovata Forssk.) seed coatings are described.